PREVALENCE OF GASTROINTESTINAL PARASITES IN STRAW-COLORED FRUIT BATS IN MAKURDI, BENUE STATE NIGERIA - Ameh, Veronica Odinya; Akura, Mercy-Grace Mhuunu; Ikye-Tor, Philomena Mde (FUDMA Journal of Sciences, 2026)
Fruit bats often referred to as flying foxes belonging to the family Pteropodidae, are ecologically significant mammals that play vital roles in pollination, seed dispersal, and maintaining ecosystem balance. Gastrointestinal parasites are organisms that live inside the digestive system of their host and feed on nutrients meant for the host. The presence of gastrointestinal parasite of fruit bat is profound and infected bats may exhibit reduced foraging activity and altered movement patterns. This research investigates the presence of gastrointestinal parasites in fruit bats within Makurdi metropolis; it aims to elucidate potential public health risks and implications in relation to fruit bat species. To achieve this, 449 fecal samples were obtained from bat roost sites in Makurdi. Fecal flotation and sedimentation techniques were carried out to check for the presence of gastrointestinal parasite ova and oocytes. The results showed a prevalence of 3.79% of gastrointestinal parasites circulating in fruit bat species in Makurdi. Three parasite types were identified: Eimeria spp, Strongyle-type nematodes, and Cryptosporidium spp. From this study, the prevalence obtained indicates that fruit bats in Makurdi metropolis are infected with gastrointestinal parasites, though with a low parasitic burden. However, the detection of Cryptosporidium spp, a known zoonotic organism, underscores the potential risk of disease transmission especially in areas where close human contact occurs. The findings from this study provide useful baseline data on the gastrointestinal parasites of fruit bat species in Makurdi and emphasize the importance of continued surveillance and public health awareness to mitigate potential public health threats.
Keywords: Fruit Bats; Gastrointestinal; Parasites; Prevalence; Makurdi